2015
DOI: 10.1016/j.ajpath.2015.04.021
|View full text |Cite
|
Sign up to set email alerts
|

WNT5A Inhibits Hepatocyte Proliferation and Concludes β-Catenin Signaling in Liver Regeneration

Abstract: Activation of Wnt/b-catenin signaling during liver regeneration (LR) after partial hepatectomy (PH) is observed in several species. However, how this pathway is turned off when hepatocyte proliferation is no longer required is unknown. We assessed LR in liver-specific knockouts of Wntless (Wls-LKO), a protein required for Wnt secretion from a cell. When subjected to PH, Wls-LKO showed prolongation of hepatocyte proliferation for up to 4 days compared with littermate controls. This coincided with increased b-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…Interestingly, a recent study examined the important role of Wnt5a in hepatocyte proliferation and liver regeneration [26]. Using the liver-specific knockout models of Wntless (Wls-LKO), Yang et al showed that when subjected to partial hepatectomy the Wls-LKO showed prolongation of hepatocyte proliferation for up to 4 days compared with littermate controls, which coincided with increased β-catenin/TCF activity and decreased expression and secretion of Wnt5a [26].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study examined the important role of Wnt5a in hepatocyte proliferation and liver regeneration [26]. Using the liver-specific knockout models of Wntless (Wls-LKO), Yang et al showed that when subjected to partial hepatectomy the Wls-LKO showed prolongation of hepatocyte proliferation for up to 4 days compared with littermate controls, which coincided with increased β-catenin/TCF activity and decreased expression and secretion of Wnt5a [26].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, noncanonical Wnt signaling was shown to be involved in the conclusion of liver regeneration post-PHx. Wnt5a was found to inhibit canonical Wnt/β-catenin signaling in cultured primary hepatocytes, and mice with liver-specific deletion of Wntless displayed continued hepatocyte proliferation for up to 4 days longer than control littermates, owing to the reduced expression of inhibitory Wnt5a 24–48 h post-PHx (90) (Figure 5). This suggests an autocrine mechanism of proliferation termination following the acquisition of required hepatocyte mass during regeneration.…”
Section: Cell Type–specific Roles Of Wnt/β-catenin Signaling In Livermentioning
confidence: 99%
“…The termination of liver regeneration in fact requires a transition from positive to negative regulation within a signaling pathway. In this path, Wnt5a seems to play a crucial role (Fan et al, ; Yang et al, ). In our model, Wnt5a showed an increase in both transplanted groups, more pronounced in iBHPs–HM group and only moderate in iBHPs–saline group, compared with sham.…”
Section: Discussionmentioning
confidence: 99%
“…The termination of liver regeneration in fact requires a transition from positive to negative regulation within a signaling pathway. In this path, Wnt5a seems to play a crucial role Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%